Efflux pumps encoding genes (adeA and adeS) in relation to antibiotic resistance pattern in Acinetobacter baumannii strains isolated from Benha university hospital - Amira E Ramadan (Egyptian Journal of Chest Disease and Tuberculosis)
Background Acinetobacter baumannii become a growing problem in hospitals as a predominant multidrug-resistant (MDR). This resistance capacity is generated by various mechanisms including efflux pumps that can direct antibiotics outwards and prevent antibiotics from affecting the bacteria.